Noninvasive assessment of pulmonary arterial capacitance by pulmonary annular motion velocity in children with ventricular septal defect. Issue 1 (December 2015) - Hayabuchi, Yasunobu; Ono, Akemi; Homma, Yukako; Kagami, Shoji
Abstract Background We hypothesized that longitudinal pulmonary arterial deformation during the cardiac cycle reflects pulmonary arterial capacitance. To examine this hypothesis, we assessed whether tissue Doppler-derived pulmonary annular motion could serve as a novel way to evaluate pulmonary arterial capacitance in pediatric patients with ventricular septal defect (VSD). Methods In this prospective study, pulmonary annular velocity was measured in children (age, 6 months–5 years) with a preoperative VSD (VSD group, n  = 35) and age-matched healthy children (Control group, n  = 23). Pulmonary artery capacitance was calculated by two methods. Systolic pulmonary arterial capacitance (sPAC) was expressed as the stroke volume/pulmonary arterial pulse pressure. Diastolic pulmonary arterial capacitance (dPAC) was determined according to a two-element windkessel model of the pulmonary arterial diastolic pressure profile. Results Pulmonary annular velocity waveforms comprised systolic bimodal (s1′ and s2′) and diastolic e' and a' waves in all participants. The peak velocities of s1′, s2′, and e' were significantly lower in the VSD group than in the Control group. On multiple regression analysis, sPAC was an independent variable affecting the peak velocities of the s1′, s2′, and e' waves (β = 0.41, 0.62, and 0.35, respectively). The dPAC affected the s1′ wave peak velocity (β = 0.34). The time durations of the s1′ and e' waves were independently determined by the sPAC (β = 0.49 and 0.27). Conclusion Pulmonary annular motion velocity evaluated using tissue Doppler is a promising method of assessing pulmonary arterial capacitance in children with VSD.